Clinical and immunological phenotypes of systemic lupus erythematosus, identified based on cluster analysis of data from 400 patients from V.A. Nasonova Research Institute of Rheumatology - E. A. Aseeva; A. M. Lila; S. K. Soloviev; E. L. Nasonov; S. I. Glukhova (Современная ревматология)
Objective: to identify clinical and immunological variants (phenotypes) of systemic lupus erythematosus (SLE) using cluster analysis.Patients and methods. The study included 400 patients with diagnosis of SLE according to the 2012 SLICC classification criteria. Patients underwent laboratory and immunological workup according to accepted standards of medical care for patients with SLE, and therapy was prescribed in accordance with disease activity.Results and discussion. Among patients, most were females (ratio of men and women – 1:10), and people of young age (34.2±11.5 years), with an average duration of illness of 6 [3; 12] years. In 98 (25%) patients with SLE, the disease debuted before the age of 18 years. Lupus nephritis (LN) was detected in 192 (48%) patients, SLE with antiphospholipid syndrome (APS) – in 48 (12%), SLE with Sjцgren's syndrome – in 44 (11%). For cluster analysis 30 clinical, 4 laboratory, 12 immunological and 10 therapeutic parameters were selected and a dendrogram was constructed with the calculation of the Euclidean distance using the Ward method. As a result, five clusters of SLE were identified: with the development of LN; with predominantly extrarenal manifestations; SLE combined with APS; SLE combined with Sjцgren's syndrome; SLE with a debut in childhood (up to 18 years of age). Clusters differed in clinical, laboratory and immunological parameters, as well as in therapy.Conclusion. Cluster analysis data made it possible to group the selected signs into five clinical and immunological variants (phenotypes) of SLE. Identification of SLE phenotypes as a set of characteristics that, individually or in combination, make it possible to determine differences between patients based on clinical, laboratory and immunological parameters, variants of the onset and course of the disease, response to therapy and prognosis, will contribute to a personalized approach in choosing the therapy, improving its long-term results, as well as quality of life and prognosis in patients with SLE.